Influence of sample measuring cell on isothermal crystallization of liquid crystalline compound forming the smectic CA* phase. (1st February 2023) - Deptuch, Aleksandra; Juszyńska-Gałązka, Ewa; Drzewicz, Anna; Piwowarczyk, Marcin; Urbańska, Magdalena; Tykarska, Marzena
ABSTRACT : Crystallization of liquid crystalline ( S )-4′-(1-methylheptyloxycarbonyl) biphenyl-4-yl 4-[7-(2, 2, 3, 3, 4, 4, 4-heptafluorobutoxy) heptyl-1-oxy]-2, 3-difluorobenzoate in isothermal conditions is investigated by polarizing optical microscopy and differential scanning calorimetry. It is shown that the sample container influences the crystallization kinetics, as a faster development of the crystal phase is observed on microscopic textures, for a sample in an electro-optic cell with a planarly aligning polymer layer, than for a sample in an aluminum pan used in a differential scanning calorimetry experiment. However, in both cases the total time of melt crystallization in the 291–303 K range is shorter than 10 min. Only at the highest investigated temperature, 305 K, the crystallization process is completed after 1.4 h because of a long initialization time. The difference with the glassforming ( S )-4′-(1-methylheptyloxycarbonyl) biphenyl-4-yl 4-[7-(2, 2, 3, 3, 4, 4, 4-heptafluorobutoxy) heptyl-1-oxy]-2-fluorobenzoate is explained based on the thermodynamic driving force of crystallization.